2014
DOI: 10.1016/j.phrp.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Mycobacterium intracellulare Using Pulsed-Field Gel Electrophoresis, Variable-Number Tandem-Repeat Analysis, Mycobacteria Interspersed Repetitive-Unit-Variable-Number Tandem Repeat Typing, and Multilocus Sequence Typing: Molecular Characterization and Comparison of Each Typing Methods

Abstract: ObjectivesMycobacterium intracellulare is the major causative agent of nontuberculous mycobacteria-related pulmonary infections. The strain typing of M. intracellulare is important for the treatment and control of its infections. We compared the discrimination capacity and effective value of four different molecular typing methods.MethodsAntibiotic susceptibility testing, hsp65 and rpoB sequencing, pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), mycobacteria interspersed repetitive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
0
5
1
Order By: Relevance
“…The overall discriminatory power of the 17-locus typing assay was calculated at 0.66. This was somewhat lower than what was reported for VNTR typing schemes in other NTM, including M. abscessus (13–18 loci, HGDI = 0.96–0.98) 29 , 49 , 50 , M. avium (5–8 loci, HGDI from 0.74 to 0.95) 44 , 51 53 or M. intracellulare (15–16 loci, 0.98–0.99) 27 , 45 , 54 , 55 . At the same time, the genetic diversity of the population studied, measured by the number of different VNTR profiles identified per study sample, was found to be rather moderate when compared to other VNTR-typed NTM (GDI = 0.35 vs 0.1–0.84) 25 , 27 , 29 , 44 , 54 56 .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The overall discriminatory power of the 17-locus typing assay was calculated at 0.66. This was somewhat lower than what was reported for VNTR typing schemes in other NTM, including M. abscessus (13–18 loci, HGDI = 0.96–0.98) 29 , 49 , 50 , M. avium (5–8 loci, HGDI from 0.74 to 0.95) 44 , 51 53 or M. intracellulare (15–16 loci, 0.98–0.99) 27 , 45 , 54 , 55 . At the same time, the genetic diversity of the population studied, measured by the number of different VNTR profiles identified per study sample, was found to be rather moderate when compared to other VNTR-typed NTM (GDI = 0.35 vs 0.1–0.84) 25 , 27 , 29 , 44 , 54 56 .…”
Section: Discussioncontrasting
confidence: 57%
“…The clustering rate, often used as a proxy for transmission or an outbreak, exceeded, with our method, 80%. This was higher than the analogous rate for M. abscessus (34.2–48.2%) 29 , 49 or M. intracellulare (31–55%) 27 , 54 , 56 and lower than for M. avium (95.6–95.9%) 25 , 44 . Given a long collection time of the study sample (16 years) and the fact that the isolates were of different origins (both environmental and clinical), and from different geographical locales, the overall high CR reflects genome homoplasy, which is a product of convergent evolution, rather than ongoing active transmission.…”
Section: Discussionmentioning
confidence: 58%
“…The second MST analysis was conducted to reconfirm the characteristics of the strains from Gyeongnam, Korea (n = 99), and the comparison with the strains from Seoul, Korea (n = 45; [ 25 ]), was conducted more precisely using 21 loci of VNTR and VNTR-MIRU excluding VNTR 11 and MIRU3 ( Figure 5 ; see also Table S2 in the Supplemental Materials ). As a result, the Gyeongnam-derived strains were found to form genetic clusters (red, green) different from those of Seoul (purple cluster) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The patterns 22 of the two analyses were similar, suggesting that VNTR may be a suitable alternative to PFGE for use in distinguishing recurrence [63]. In addition, M. intracellulare was subjected to antibiotic susceptibility testing, sequencing of the hsp65 and rpoB genes, PFGE, Multilocus sequence typing (MLST), MIRU-VNTR, and VNTR [64]. The discrimination power for M. intracellulare was found to be higher in order of PFGE, VNTR, MLST.…”
Section: Comparison Of Pfge With Other Genotyping Methodsmentioning
confidence: 95%
“…The discrimination power for M. intracellulare was found to be higher in order of PFGE, VNTR, MLST. Furthermore, it was reported to be useful for distinguishing recurrence [64].…”
Section: Comparison Of Pfge With Other Genotyping Methodsmentioning
confidence: 99%